2016
DOI: 10.1038/eye.2016.59
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of retinopathy in children younger than 12 years of age: implications for the diabetic eye screening guidelines in the UK

Abstract: Aim To assess whether the current starting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
10
1
Order By: Relevance
“…DR, although a common complication in type 1 and type 2 diabetes, is rarely observed in children and young adults, and this has been attributed to the fact that several years are required from the onset of diabetes to the development of clinically significant retinal changes [202]. A retrospective analysis of 143 patients aged 12 years or younger, who attended diabetic eye screening for the first time in a Birmingham DR screening programme, identified only 12 patients (8.4%) with DR (mild DR without diabetic maculopathy); no patient was identified with sight-threatening DR at the initial assessment [202].…”
Section: Section 7: Diabetic Retinopathy In Children and Young Adultsmentioning
confidence: 99%
“…DR, although a common complication in type 1 and type 2 diabetes, is rarely observed in children and young adults, and this has been attributed to the fact that several years are required from the onset of diabetes to the development of clinically significant retinal changes [202]. A retrospective analysis of 143 patients aged 12 years or younger, who attended diabetic eye screening for the first time in a Birmingham DR screening programme, identified only 12 patients (8.4%) with DR (mild DR without diabetic maculopathy); no patient was identified with sight-threatening DR at the initial assessment [202].…”
Section: Section 7: Diabetic Retinopathy In Children and Young Adultsmentioning
confidence: 99%
“…Probably, this results from better metabolic control effect, more physiological treatment using CSII by means of an insulin pump, more frequent use of continuous glucose monitoring, and more active and aggressive treatment based on monitoring trends. However, the analysis from the United Kingdom demonstrated that 9.5% of children under 12 years old had signs of background DR [ 10 ]. Our study also included children with poor metabolic control, but none of them had any signs of DR (neither in fundoscopy nor on fundus color photography), even after 14 years of T1D duration.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Furthermore, a recent large US study has shown an increase of 20% (95% CI 6%–35%) of the hazard of DR for every one-point rise of HbA1c in children with T1D, and what is very important is that DR in children seems to progress rapidly. 16 However, it may be still controversial if all of the above is related to longer duration of T1D or to the influence of puberty. To eliminate any doubts we have decided to carry out an additional analysis to compare children with the same duration of diabetes.…”
Section: Discussionmentioning
confidence: 99%